Elasticity, militancy, and infection : metaphorical argumentation in the trial against the German Communist Party, 1954–56 - Pankakoski, Timo (Taylor & Francis, 2025)
This article analyzes the epoch-making trial against the German Communist Party (KPD) in 1954-56 - a process with unmistakable political, ideological, and political-theoretical aspects. Both the government and the party's representatives used metaphorical arguments to publicly state their case for or against the eventual party ban. Citing classics of Marxism-Leninism for evidence, the government blamed the KPD for planning a violent revolution and described its activities metaphorically in military terms. The party retorted by ridiculing the government for reading metaphors literally and, more methodologically, rejected the government's non-contextual approach as ‘Talmudism' and ‘hodgepodge', while simultaneously promoting the Leninist doctrine of tactical ‘elasticity' to secure their own argumentative leeway. The government depicted communism as an infection to be removed by amputation - a metaphor the KPD reappropriated and used to present itself as integral to West-German democracy and the guarantor of German unification. Rather than being superficial rhetoric, these interlinked metaphorical arguments captured the gist of the ideological disagreement. The metaphors can be understood properly only by reading them together and considering the underlying argumentative functions that are identifiable by analyzing the explicit proposition each side put forth. The metaphors transcended mere legal argumentation and exemplify the trial’s inherent political nature.